Female leadership, performance, and governance in microfinance institutions - Reidar Øystein Strøm; Bert D'Espallier; Roy Mersland (Journal of Banking & Finance, 2014)
This paper investigates the relations between female leadership, firm performance, and corporate governance in a global panel of 329 Microfinance Institutions (MFIs) in 73 countries covering the years 1998–2008. The microfinance industry is particularly suited for studying the impact of female leadership on governance and performance because of its mission orientation, its entrepreneurial nature, diverse institutional conditions, and high percentage of female leaders. We find female leadership to be significantly associated with larger boards, younger firms, a non-commercial legal status, and more female clientele. Furthermore, we find that a female chief executive officer and a female chairman of the board are positively related to MFI performance, but this result is not driven by improved governance.
Keywords: 650